Study of Bioactivity and Physicochemical Properties of New Metal Chelates of Schiff Base Derived from 4-Aminoantipyrine with Cysteine - Hussein, Kawther Adeeb; Ali, Dina Naseer; Faeq, Marwa (Universitas Gadjah Mada, 2026)
Transition metallic complexes Cr, Co, Ni, Mn, and Cu were designed and prepared using a new bidentate chelator ligand from 4-aminoantipyrine with cysteine. The products were characterized using various analytical, spectroscopic, and theoretical methods. According to the various analysis data, the azomethine-Schiff base chelator linked with metallic cations as a neutral bidentate chelator exhibited distorted octahedral and tetrahedral structures, with protonated and deprotonated carboxyl oxygen and azomethine nitrogen atoms in a molar ratio of 1:2 metal: ligand in a structure of [M(L)2Cl2]·nH2O and [M(L)2]·Cl2nH2O. According to mass spectroscopy, the molecular weights of the azomethine-Schiff base closely match those estimated by m/z. Additionally, Fourier-transform infrared (FTIR), ultraviolet-visible (UV-vis), 1H-NMR, and 13C-NMR spectra, LC-MS, magnetic moment, and molar conductance were used to study the structure of the azomethine-Schiff base ligand and metallic complexes. The antibacterial activity was tested against Staphylococcus aureus, Streptococcus pyogenes, Escherichia coli, and Acinetobacter baumannii, while the antifungal activity was evaluated against Candida albicans, Candida parapsilosis, Candida lusitaniae, and Candida tropicalis. The free ligand showed negligible activity, whereas its metal complexes exhibited moderate to strong antimicrobial effects, confirming that metal coordination significantly enhances biological potency.